Impact Of Educational Status of Parents on Nutritional Status of Adolescent Girls-A Cross Sectional Study - Sujit K Singh; Gagan Garg; Sanjeev Davey; Santosh Kumar Raghav; Khursheed Muzammil; Jai Vir Singh (Medsci Publications, 2014)
Background: Adolescent is a period where significant growth changes occur necessitating optimum nutritional requirement. During adolescence 20% of adult height attained and 50% of adult bone mass gained. Girls deposit twice as much body fat as boys at this time and boys double their lean body mass. As a result nutrition requirement peak in adolescent. Failure to achieve optimum nutrition intake at this time can potentially retard physical growth, intellectual capacity and sexual maturation. Objective of this study was to study the effects of parental education on nutrional status of the adolescent girl. Material and Methods: A community based cross sectional study was carried out among 400 randomly selected adolescent girls belonging to makhinagarkhalapar block which is the field practice area of Muzaffarnagar Medical College, Muzaffarnagar (UP). The data was recorded in pre-designed and semi-structured Questionnaire. Results: The proportion of adolescent girls aged 10-14 years and 15-19 years comprised of 41.2% and 58.8% respectively. Under nutrition was maximum (50%) in adolescent girls whose mothers were illiterate followed by 41% in girls whose mothers were just literate (p<0.05). Similarly the prevalence ofunder nutrition was maximum (100%) in adolescent girls whose fathers were illiterate. Conclusion: This study found strong association between the nutritional status of adolescent girls and education of parents. Illiteracy of their parent is the main factor of malnutritionamong adolescents.